(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Pseudomonas aeruginosa has assumed an increasingly prominent role as the etiological agent in a variety of serious infections in hospitalized patients. Pseudomonas aeruginosa strains produce three distinct types of bacteriocins (bactericidal substances). Bacteriocins of P. aerugonosa strains can be classified according to their morpology, or according to functions into pore forming pyocin and DNase activity–pyocins. Objectives:To type by a molecular method local isolates of Pseudomonas aeruginosa utilizing the genes encoding for the potent bacteriocin (pyocin). Methods: Fifty bacterial isolates of P. aeruginosa were re-identified by standard bacteriological methods and were subjected to PCR-amplification for the genes responsible for the production of three bacteriocins (pyocin S1, S2, and S3). Results:Out of the fifty local isolates of P. aeruginosa enrolled in this study there were forty five (45) isolates which showed the presence of the genes encoding for the two mentioned bacteriocins (S1 and S2) corresponding to 95% of the isolates and there were forty five (41) isolates showed the presence of the gene encoding for the pyocin S3 corresponding to 82% of the isolates. Conclusions:The present work showed a high genotypic relatedness of the studied clinical isolates of P. aeruginosa and it also emphasized the ability of the use of molecular typing of pyocins as more advanced and accurate methods for typing purposes and epidemiological studies. Key words: Pyocins, Bacteremia, bacteriocins, polymerase chain reaction (PCR), electrophoresis